Incidental pancreatic nodule in a patient with Tuberous Sclerosis - Barbosa, André Gustavo da Silva; Lima, Isabelle Pereira; Pinto, João Macedo Holanda; Leitão, Lucas de Souza Antunes; Cunha, Ana Beatriz Albuquerque da; Reinaldo, Bruna Maciel Cardoso Ramos; Furtado , Raimundo Hugo Matias; Cavalcanti, Fernando Jorge Diniz (Seven Editora, 2024)
ET is a genetic disorder that leads to a disturbance in cell proliferation and migration related to variable clinical manifestations, ranging from benign lesions to malignant tumors. Most ET patients diagnosed with NETs have pancreatic involvement, however the presence of these tumors in other organs should be considered as part of the disease phenotype. Recent studies have shown that the majority of tuberous sclerosis patients with pancreatic NETs have a germline pathogenic variant in the TSC2 gene. In the present report, the patient had a tumor in the caudal region of the pancreas that was asymptomatic. Current surgical recommendations for non-functional pancreatic NETs indicate the need for surgical removal when they are more than 20 mm in size or have very rapid growth. In this case, the area of the tumor made surgical removal necessary. DOI:https://doi.org/10.56238/sevened2024.001-007